UJI AKTIVITAS LARVASIDA EKSTRAK DAUN JARAK KEPYAR (Ricinus communis L.) TERHADAP LARVA NYAMUK Aedes aegypti - Wahyu Wira Utami; Aktsar Roskiana Ahmad; Abd. Malik (Jurnal Fitofarmaka Indonesia, 2016)
Castor Plant (Ricinus communis L.) belongs to Euphorbiaceae family. In medicine has been used as antioxidant, antihistaminic, antifertility, antimicrobial, antidiabetic, antiinflammatory, antipyretic, and it has activities to larvacidal, molluscicidal and insecticidal. The aim of this study was to determine the level of mosquito larva (Aedes aegypti) mortality after giving of ethanolic extract showed with LC50. Extract obtained by maceration method, rendamen ethanolic extract obtained as much as 6.073%. This research uses 110 instar, III larvae of mosquito (Aedes aegypti), divided into test solution are made with 3 concentrations (10 µg/mL, 100 µg/mL, 1000 µg/mL), positive control using Abate and negative control using water. Observations were made after 24 hours of treatment. Toxicity test results shows ethanolic extract is an extract that is active as Larvacidal showed LC50 as much as 138,995 ± 1,5 µg/mL < 1000 µg/mL. Based on qualitative testing of the chemical component using TLC method known ethanolic extract of Castor Plant (Ricinus communis L.) leaves contain alcaloids, saponins and flavonoids.